Description of terminal substitutional solid solutions using the sublattice model. (December 2019) - Joubert, Jean-Marc; Crivello, Jean-Claude
Abstract: The case of the substitutional solid solutions based on elements possessing several crystallographic sites is discussed. It is concluded that, at least in some cases, especially when the solution domain is large and when strong differences of site occupancies are observed between the different sites, the sublattice model should be used as it is the case for interstitial solid solutions or non-stoichiometric intermetallic compounds. Results of experimental site occupancies are presented and compared with these obtained from the DFT calculations from which the configurational entropy can be calculated. Comparison of the enthalpy and entropy of the solid solutions is made with the available thermodynamic assessments. The β-U phase in U–Pu system is addressed but the most important cases are α-Mn and β-Mn solid solutions in different systems such as Mn–Re, Fe–Mn, Al–Mn and Al–Fe–Mn. These phases are particularly detailed and conclusions are given relative to their thermodynamic modeling emphasizing the need to use the sublattice model.